The conceptual design of very light jet - Edi, P.; Yusuf, K.; Ghani, A.R.A. (2009)
This paper intends to present the conceptual design of very light jet (VLJ) aircraft in the university level. The design process that covers by this paper is just from conceptual approach. Current technical information of the business jet in the market will be studied for competitor analysis purpose. After that, the calculation process will take part, like initial sizing, performance sizing, initial sizing of main component, weight breakdown, cg (centre of gravity) position and aircraft performance. This paper will only concentrate on conceptual design, the next stage of design can be continuing in future with the data from this paper.